A pilot study on the efficacy of Valeriana officinalis mother tincture and Valeriana officinalis 3X in the treatment of attention deficit hyperactivity disorder - Radmila Razlog; Janice Pellow; Janice Pellow (AOSIS, 2012)
Attention deficit hyperactivity disorder (ADHD) is an increasingly prevalent behavioural disorder characterised by inattention, impulsivity and hyperactivity. Valeriana officinalis is a botanical medicine that has been found to be beneficial in the treatment of disorders characterised by restlessness. To date, no research has been conducted on homeopathic preparations of Valeriana officinalis for this condition. The aim of this three-week, double-blind, placebo-controlled pilot study was to determine the efficacy of homeopathic Valeriana officinalis mother tincture (MT) and 3X potency on ADHD. Thirty children between the ages of five and 11 years, pre-diagnosed with ADHD, were recruited. Valeriana officinalis MT (n = 10), 3X (n = 10) or placebo (n = 10) were administered orally three times a day for two weeks. Efficacy was assessed by the Barkley and DuPaul teacher rating scale, the children's checking task and the parent symptom questionnaire scores on day 1 (prior to treatment), at the end of weeks two and three (with treatment), and then after the third week following no treatment. A statistically significant improvement was found in the participants' behaviour in the MT and 3X groups, with particular reference to sustained attention, anxiety and impulsivity and/or hyperactivity. Preliminary findings suggested that Valeriana officinalis MT and 3X may have applications in the management of ADHD.Aandagsgebrek-hiperaktiwiteitsindroom (AGHS) is toenemend 'n algemene gedragsongesteldheid, wat gekenmerk word deur onoplettendheid, impulsiwiteit en hiperaktiwiteit. Daar is vasgestel dat Valeriana officinalis 'n plantaardige medisyne is wat voordelig kan wees in die behandeling van ongesteldhede wat gekenmerk word deur rusteloosheid. Tot op hede is geen navorsing uitgevoer op die gebruik van homeopatiese preparate van Valeriana officinalis vir hierdie ongesteldheid nie. Die doel van hierdie drieweeklange, dubbelblinde, troosmedisyne-gekontroleerde loodsstudie was om die effektiwiteit van homeopatiese Valeriana officinalis Moertinktuur (MT) en 3X sterkte vir die behandeling van AGHS te bepaal. Dertig kinders tussen die ouderdomme van 5 en 11 jaar, wat vantevore gediagnoseer is met OGHO, is gewerf. Valeriana officinalis MT (n = 10), 3X (n = 10) of troosmedisyne (n = 10) is mondeliks drie keer per dag vir twee weke toegedien. Effektiwiteit is gemeet op dag 1 (voor behandeling), aan die einde van weke twee en drie (tydens behandeling), en na die derde week sonder behandeling deur middel van tellings wat behaal is op die Barkley and DuPaul teacher rating scale, die children's checking task en die parent symptom questionnaire. 'n Statisties beduidende verbetering is gevind in die gedrag van die deelnemers in die MT en 3X groepe, in die besonder met betrekking tot volgehoue oplettendheid, angstigheid en impulsiwiteit en/of hiperaktiwiteit. Voorlopige bevindinge dui daarop dat Valeriana officinalis MT en 3X moontlik gebruik kan word in die behandeling van AGHS.